Paternal Roles in Breastfeeding in Jakarta, Indonesia: A Mixed-method Approach - Februhartanty, Judhiastuty; Muslimatun, Siti; Shankar, Anuraj H; Djakababa, Nelden; Suradi, Rulina (Jurusan Gizi, Fakultas Kedokteran, Universitas Brawijaya Malang, 2020)
Abstract We explored paternal roles in timely breastfeeding initiation and exclusive breastfeeding practices in Jakarta using a mixed-methods approach in sequence of focus group discussions (FGDs – phase 1) and a quantitative survey (phase 2). The study population was parents with infants aged below 6 months. Data on paternal roles, maternal attributes, and breastfeeding practices were collected from 43 purposively selected parents in phase 1 and 536 couples in phase 2. FGDs provided insights to finalize the questionnaire for the survey. Nine paternal roles were identified: 1-accompanying the mother during antenatal and postnatal visits, 2-suggesting places for health checkups and delivery, 3-seeking information about child nutrition, 4-accompanying the mother during delivery, 5-facilitating psychological support of the mother, 6-childcare involvement, 7-engagement in childcare discussions, 8-involvement in decisions about infant feeding mode, and 9-enthusiasm for fatherhood. Roles 3 (aOR=1.65; 95%CI=1.07 to 2.54) and 9 (1.59; 1.04-2.44) were positively associated with timely initiation of breastfeeding. Role 8 was positively associated with exclusive breastfeeding (1.69; 1.10-2.60), but roles 2 (0.49; 0.32-0.76) and 5 (0.97; 0.41-0.64) were negatively associated with exclusive breastfeeding. Fathers played roles in breastfeeding practices under study. Fathers need a tailored breastfeeding promotion to stimulate necessary support for breastfeeding mothers. Keywords: initiation of breastfeeding, exclusive breastfeeding, fathers, mixed-methods approach, Indonesia